Synthesis of Biodiesel from Waste Cooking Oil Using Heterogeneous Catalyst (CaO) Based on Duck Eggshell with Transesterification Reaction - Susvira, Dian; Hartono, Rudi; Fauzantoro, R. A. (Jurnal Kartika Kimia, 2022)
Biodiesel is produced from esterification and transesterification reactions of various vegetable oils such as coconut oil, palm oil, seed oil, soybean oil, etc. Waste cooking oil has the potential as a raw material for making biodiesel due to its abundant availability. The use of the CaO catalyst from duck eggshells can increase biodiesel quality. This study aimed to obtain the best catalyst with a high yield in biodiesel production using the transesterification method. The initial stage begins with activating the impregnated duck eggshell catalyst with various concentrations of KOH in distilled water (10 g KOH/100 mL, 15 g KOH/100 mL, 20 g KOH/100 mL, and 25 g KOH/100 mL). Followed by biodiesel synthesis steps using temperature variations in transesterification (45˚C, 55˚C, and 65˚C) in reaction times of 1, 2 and 3 hours using 2% catalyst concentration to the amount of waste cooking oil and a molar ratio of methanol: oil (7:1). The experimental results showed that transesterification of waste cooking oil could be improved with the presence of a CaO heterogeneous catalyst. The values of density, Free Fatty Acid (FFA), viscosity, and the acid number obtained was adjusted to the parameters using SNI:7182:2015. Only the total ester parameter (96.02%) and the cetane number (40.4) did not meet the requirements. Keywords: biodiesel, duck eggshell, waste cooking oil